Alteration patterns of trabecular bone microarchitectural characteristics induced by osteoarthritis over time - Lee JH (Dove Medical Press, 2012)
Joo Hyung Lee,1 Keyoung Jin Chun,2 Han Sung Kim,3 Sang Ho Kim,4 Paul Han,3 Yongtae Jun,1 Dohyung Lim11Department of Mechanical Engineering, Sejong University, Seoul, South Korea; 2Gerontechnology Research Group, Korea Institute of Industrial Technology, Cheonan, South Korea; 3Department of Biomedical Engineering, Yonsei University, Wonju, South Korea; 4Department of Bioengineering and Department of Surgery, National University of Singapore, SingaporeAbstract: Information regarding the alteration of trabecular bone microarchitecture, which is one of the important criteria to estimate bone condition, induced by osteoarthritis (OA) is sparse. The current study therefore aimed to identify and quantify patterns of alterations in trabecular bone microarchitectural characteristics at tibial epiphysis induced by OA using in vivo microcomputed tomography. Fourteen 8-week-old female Sprague Dawley rats were randomly divided into control (n = 7) and OA (n = 7) groups. Rats in the OA group were administered monoiodoacetate into the knee-joint cavity. The tibial joints were scanned by in vivo microcomputed tomography at 0, 4, and 8 weeks after administration. Two-way analysis of variance with Tukey’s honestly significant difference post hoc test was carried out for statistical analyses. The results showed that patterns of alterations in the trabecular bone microarchitectural characteristics in the OA group were not different from those in the control group from 0 to 4 weeks (P > 0.05), but differed from 4 to 8 weeks (P < 0.05). In particular, both trabecular bone thickness and trabecular bone separation distributions over time (4–8 weeks) differed significantly (P < 0.05). These findings suggest that the patterns of bone microarchitecture changes brought about by OA should be periodically considered in the diagnosis and management of arthritic symptoms over time. Improved understanding of the alteration pattern on trabecular bone microarchitecture may assist in developing more targeted treatment interventions for OA.Keywords: osteoarthritis, in vivo microcomputed tomography, trabecular bone microarchitectural characteristics, trabecular bone thickness distribution, trabecular bone separation distribution